Eco-friendly bioactive β-caryophyllene/halloysite nanotubes loaded nanofibrous sheets for active food packaging. (March 2023) - Ullah, Azeem; Sun, Lei; Wang, Fei-fei; Nawaz, Hifza; Yamashita, Kentaro; Cai, Yingying; Anwar, Faiza; Khan, Muhammad Qamar; Mayakrishnan, Gopiraman; Kim, Ick Soo
Abstract: We fabricated Zein/polycaprolactone (PCL) electrospun nanofiber sheets incorporated with different concentrations of β-caryophyllene loaded into halloysite (HNT) nanotubes as an eco-friendly, bioactive food packaging material. We obtained heterogeneous fibers with flat ribbon-like morphology. The loading of β-caryophyllene/HNT increased the fiber diameters from ∼900 nm to ∼1100 nm. The nanofiber showed improved thermal and mechanical performance upon incorporating β-caryophyllene/HNT. The water vapor permeability decreased due to a decrease in the porosity of the nanofiber sheets. The β-caryophyllene/HNT loaded nanofiber showed good DPPH free radical scavenging and was effective against both gram-positive B.subtilis and gram-negative E.coli bacteria subjected to agar disc diffusion test and time-kill study. The initial release of β-caryophyllene from the 5%, 10%, and 20% loaded nanofiber sheets was ∼22%, ∼25%, and ∼31% within 12 h, and ∼63%, ∼69%, and ∼77% after 120 h indicating a sustained slow release for long term bioactivity. The WST-1, LDH, and cell adhesion properties of β-caryophyllene/HNT-loaded nanofiber render them biocompatible and nontoxic. Composting experiment reveals the eco-friendly nature of the fabricated nanofiber sheets as they all lose their fibrous morphology after 21 days of composting and a mass loss of ∼65% for Zein/PCL nanofibers and ∼63%, ∼55%, and ∼48% for 5%, 10%, and 20% β-caryophyllene/HNT loaded Zein/PCL nanofiber sheets. During the application test for postharvest quality preservation of strawberries, the strawberries covered in Zein/PCL-20 showed the best-preserved quality after 4 days of storage at 25 °C in 40% humidity. The physicochemical, biological, and application tests demonstrated the potential of the prepared nanofiber sheets as a potential bioactive food packaging material. Graphical Abstract: ga1 Highlights: Bioactive nanofibrous packaging were obtained by electrospinning. β-caryophyllene with antioxidant and antibacterial capacity was included nanofibers. Compositing reveals eco-friendly nature of nanofiber sheets. β-caryophyllene addition improved the antioxidant and antibacterial activity. The fibers retarded the postharvest quality decay in strawberries.